Extensive Visually-Significant Stellate-Like Pseudoexfoliative Deposition on an Intraocular Lens Implant of Pseudophakic Eye: Insights for Unusual Presentation [Response to Letter] - Aleshawi A; Al Qudah MA; Alazmi H; Al Sharie A; Elnagar Jnr HS; Alzoubi H; Almutairi S; Al Beiruti S; Al-Dwairi R (Clinical Optometry)
Abdelwahab Aleshawi,1 Mohammad Ali Al Qudah,1 Hamad Alazmi,2 Ahmed Al Sharie,2 Haya Sufyan Elnagar Jnr,3 Hosni Alzoubi,1 Saad Almutairi,2 Seren Al Beiruti,1 Rami Al-Dwairi1 1Department of Special Surgery, Division of Ophthalmology, Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, Jordan; 2Department of Ophthalmology, Ministry of Health, Kuwait City, 12009, Kuwait; 3Division of Ophthalmology, Department of Special Surgery, School of Medicine, The University of Jordan, Amman, 11942, JordanCorrespondence: Abdelwahab Aleshawi; Rami Al-Dwairi, Department of Special Surgery, Division of Ophthalmology, Faculty of Medicine Jordan University of Science and Technology, P. O. Box: 3030, Irbid, 22110, Jordan, Tel +962795355056, Fax +962 2 7201064, Email abdelwahhabjamal@yahoo.com; ramialdwairi@yahoo.com